Treatment of the Atrophic Upper Jaw: Rehabilitation of Two Complex Cases - Andrea Enrico Borgonovo; Andrea Marchetti; Virna Vavassori; Rachele Censi; Ramon Boninsegna; Dino Re (Hindawi Limited, 2013)
In reconstructive surgery, the fresh frozen homologous bone (FFB) represents a valid alternative to the autologous bone, because FFB allows bone regeneration thanks to its osteoinductive and osteoconductive properties. The purpose of this work is to describe the surgical-implant-prosthetic treatment of two complex cases using FFB. In particular, fresh frozen homologous bone grafts were used to correct the severe atrophy of the maxilla, and, then, once the graft integration was obtained, implant therapy was performed and implants placed in native bone were immediately loaded.